Facing reality: A survey of methods instructors' perspectives on world language teacher development. (27th February 2019) - García, Paul A.; Moser, Kelly M.; Davis‐Wiley, Patricia
Abstract : This study reports the findings of a national survey on PreK–12 world language teacher development (WLTD), and was conducted in order to assist the profession as simultaneously it confronts the intersecting challenges of a nationwide world language (WL) teacher shortage, strives to meet new teacher preparation standards, and ensures the future of language teaching and learning in American schools. The 164 methods instructors (MIs) described the contexts in which they address pre‐service candidates' needs and aspirations, and shared their opinions on the current status of WLTD, the perceived impediments to promoting its well‐being, and the structures that are necessary to guarantee success in providing superior teachers for tomorrow's language learners. Implications for the profession are explored. The Challenge: Anecdotally, methods instructors have suggested that a crisis exists in world language teacher development (WLTD) affecting the recruitment and retention of teacher candidates. How do empirical data derived from a national survey inform an understanding of this crisis? What implications for preparing future WL teachers may be drawn?